Optimization of residual herbicide applications - Meyeres, Tyler Paige (Kansas State University, 2024)
Optimization of residual herbicide applications is critical to control of herbicide-resistant Palmer amaranth (Amaranthus palmeri S. Watson) and waterhemp (Amaranthus tuberculatus [Moq.] Sauer). In this dissertation, one greenhouse study and three field studies were established to optimize residual herbicide applications. The objective of greenhouse trial was to evaluate the response of multiple-resistant Palmer amaranth to combinations of PS II- and HPPD-inhibitor herbicides. The first field experiment was established to quantify the effect of application timing and spray volume on residual herbicide efficacy in corn. The second field experiment was established to compare Palmer amaranth control with residual herbicides applied preemergence (PRE) or postemergence (POST) in Enlist (2,4-D-resistant) and XtendFlex (dicamba-resistant) cotton systems in Kansas. The final field trial was established to compare the impact of environmental conditions on the efficacy of VLCFA-inhibiting herbicides when applied at various times throughout the growing season. In the greenhouse trial, PRE applications of metribuzin alone, metribuzin combinations, and atrazine + mesotrione resulted in 61 to 87 % control of a Palmer amaranth population resistant to TIR1-, EPSPS-, HPPD-, ALS-, PS II-, and PPO-inhibiting herbicides. POST treatments of atrazine alone and combinations with metribuzin resulted in 40 to 60% control of the same Palmer amaranth population. These results indicate herbicide combinations can be useful to manage multiple-resistant Palmer amaranth, even if resistance to those herbicides has been confirmed. In the corn trial, Resicore (clopyralid + acetochlor + mesotroine) and TriVolt (isoxaflutole + thiencarbazone-methyl + flufenacet) were applied at 56, 122, and 187 L ha⁻¹ in PRE-only or PRE followed by (fb) POST systems in 2021 (Colby and Ottawa, KS) and 2022 (Manhattan, Ottawa, and Scandia, KS). Palmer amaranth control was 94% or greater in Colby throughout the growing season. Resicore provided greater Amaranthus control than TriVolt in no-till systems. Amaranthus control was greater in PRE fb POST systems as compared to PRE-only systems. Spray volume did not effect weed control apart from waterhemp control in Ottawa 2021, where Resicore applied at 56 L ha⁻¹ provided less control than TriVolt applied at 56 L ha⁻¹ and Resicore applied at 187 L ha⁻¹. Data suggests that improper herbicide selection may be of greater consequence than spray volume for residual weed control. Applications in the cotton trial included PRE fb early POST (EPOST) fb late POST (LPOST) in 2021 and PRE fb EPOST in 2022. In 2021, pendimethalin was applied as a blanket PRE. The EPOST application in 2021 included acetochlor, dimethenamid-P, or S-metolachlor + 2,4-D or dicamba or the trait premix, which was glyphosate + 2,4-D or dicamba + S-metolachlor, applied alone. In 2021, the LPOST included glyphosate + 2,4-D or dicamba. In 2021, the LPOST included glyphosate + trait herbicide. In 2022, PRE herbicides were fluometuron or fluometuron + acetochlor, dimethenamid-P, S-metolachlor, or pendimethalin fb EPOST including glyphosate + trait herbicide or in combination with residual herbicides. In 2021, there were no differences in end of season Palmer amaranth control (48 to 71%) observed among residual herbicides as long as more than one herbicide application was utilized. In 2022, Enlist systems provided less control than XtendFlex systems. The greatest control was observed when two applications of residual herbicides were utilized as compared to no over lapping residual apart from two applications of pendimethalin. Results indicate cotton herbicide trait system influences Palmer amaranth control; but, residual herbicide selection, multiple applications, and layered residual herbicides may be of greater importance. To fulfill the objective of the final field trial, a bare-ground field experiment was established in Manhattan, KS in 2021 and 2022 where acetochlor, dimethenamid-P, pyroxasulfone, and S-metolachlor were applied at various dates throughout the growing season to capture variations in rainfall and temperature. The effects of rainfall and accumulated soil growing degree days (SGDD) on the probability of successful weed control were tested by subjecting binary responses (greater or less than 80%) of each herbicide to logistic regression. Excessive rainfall and/or elevated temperatures decreased the probability of successful control of Palmer amaranth with acetochlor, dimethenamid-P, pyroxasulfone, and S-metolachlor, but pyroxasulfone and S-metolachlor may have an advantage at high temperatures and high rainfall. In a scenario, where the rainfall forecast is predicting little rainfall within 3 WAT, pyroxasulfone and S-metolachlor may not be the most effective options. However, acetochlor may be the best fit for hot and dry conditions, as less accumulated rainfall was required to achieve high probability of successful weed control. Dimethenamid-P had a disadvantage in hot and dry conditions but was more likely to have >80% control in cool and wet conditions, indicating dimethenamid-P may be a better fit at plating or prior to planting of corn and soybeans when conditions are cooler.
Keywords: Weed managment in corn; Weed management in cotton; Residual herbicides; Effect of environment on residual herbicides; Management of herbicide-resistant Palmer amaranth